Excessive Daytime Sleepiness in Obstructive Sleep Apnea. Mechanisms and Clinical Management - Lal, Chitra (Ann Am Thorac Soc, 2021)
Many patients with obstructive sleep apnea (OSA) experience excessive daytime sleepiness (EDS), which can negatively affect daily functioning, cognition, mood, and other aspects of well-being. Although EDS can be reduced with primary OSA treatment, such as continuous positive airway pressure (CPAP) therapy, a significant proportion of patients continue to experience EDS despite receiving optimized therapy for OSA. This article reviews the pathophysiology and clinical evaluation and management of EDS in patients with OSA. The mechanisms underlying EDS in CPAP-treated patients remain unclear. Experimental risk factors include chronic intermittent hypoxia and sleep fragmentation, which lead to oxidative injury and changes in neurons and brain circuit connectedness involving noradrenergic and dopaminergic neurotransmission in wake-promoting regions of the brain. In addition, neuroimaging studies have shown alterations in the brain’s white matter and gray matter in patients with OSA and EDS. Clinical management of EDS begins with ruling out other potential causes of EDS and evaluating its severity. Tools to evaluate EDS include objective and self-reported assessments of sleepiness, as well as cognitive assessments. Patients who experience residual EDS despite primary OSA therapy may benefit from wake-promoting pharmacotherapy. Agents that inhibit reuptake of dopamine or of dopamine and norepinephrine (modafinil/armodafinil and solriamfetol, respectively) have demonstrated efficacy in reducing EDS and improving quality of life in patients with OSA. Additional research is needed on the effects of wake-promoting treatments on cognition in these patients and to identify individual or disorder-specific responses.